The Effect of Religious Belief on Depression and Hopelessness in Advanced Cancer Patients - Kavak Budak, Funda (Journal of religion and health, 2021)
This study was conducted to determine the effect of religious belief on depression and hopelessness in advanced cancer patients. The sample size of this cross-sectional study was determined as 267 as a result of the power analysis. The study was carried out between February 2018 and December 2018. “The Patient Information Form”, “The Religious Attitude Scale”, “The Beck Depression Inventory (BDI)”, and “The Beck Hopelessness Scale (BHS)” were used to collect the data. It was determined that the total mean score of the cancer patients participating in the study for Religious Attitude Scale was 4.51 ± 0.44 (high level), their total mean score for depression inventory was 19.06 ± 9.38 (moderate level), and their total mean score for hopelessness scale was 10.23 ± 1.94 (moderate level). In the study, the difference between the religious beliefs and depression and hopelessness levels of the cancer patients was statistically significant (p < 0.05). In the study, it was determined that depression and hopelessness levels of cancer patients were moderate and their religious beliefs were high. It is recommended for healthcare professionals to add spirituality to healthcare in order to provide the spiritual relief of cancer patients.